DNA Barcoding of Sangihe Nutmeg (Myristica fragrans) using matK Gene - TRINA EKAWATI TALLEI; BEIVY JONATHAN KOLONDAM (Bogor Agricultural University, Indonesia, 2015)
Nutmeg (family: Myristicaceae) is a plant that originated from Banda islands and is widely cultivated in several places in the world. Secondary metabolites of this plant have a high value because of their benefits for the health, food, and beauty industries. This study aims at developing DNA barcode for nutmeg (Myristica fragrans) using standard recommended fragment of matK (maturase K) gene. Universal matK primer pairs were used to amplify 889 bp DNA fragment. BLAST search from NCBI site showed that Sangihe nutmeg has 100% identity with Myristica fatua, M. maingayi, and M. globosa. It also has 3 nucleotides difference with Rivola sebifera (identity 99.58%) and 4 nucleotides difference with Knema laurina (identity 99.43%). It can be inferred from this study that single locus of matK gene cannot be used to differentiate species in Myristica; it can only be used to differentiate the genus level within family Myristicaceae.